(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In a report, a potential association between utilizing social media and different facets of psychological well-being was defined (anxiety, negative attitude, self-control, positive well-being, and overall health). The survey comprised 50 Indian university students aged 18-21 years. The research explored potential interactions between each factor and the use of social media. For data collection, the general psychological well-being index and an Android app named Rescue time were used. The Correlation Coefficient (r) of Karl Pearson was used for research. The findings revealed substantial detrimental associations between the use of self-control social media and the beneficial use of welfare social media no major adverse connexons were found between the use of social media and other affective conditions.